Acute renal failure in the onset of pseudomembranous colitis - S. G. Alexandrova; L. V. Bychkova; M. R. Aleksandrova; R. R. Politidis; A. S. Zhuravleva; N. D. Kisliy (Лечащий Врач)
Pseudomembranous colitis in recent years has become a fairly aggressive and widespread form of infection associated with the use of antibacterial therapy, refers to the most severe inflammatory bowel diseases, the cause of which is the grampositive sporeforming bacterium Clostridium difficile. The main symptoms of pseudomembranous colitis include: frequent watery loose stools, fever (up to 3-40 °C), abdominal pain. This article presents a clinical observation of a patient with pseudomembranous colitis, the peculiarity of which is that the patient had no stool disorder and no abdominal pain against the background of prolonged subfebrility (1.5 months). The debut of the disease began with a collapse, a convulsive attack, the phenomena of acute kidney damage, which did not allow for a timely correct diagnosis. Women received inpatient care, examined by many specialists, including a urologist, an infectious disease doctor, received therapy with linezolid (400 mg × 2 times a day – 10 days), bakperazone (1 g × 2 times a day), meropenem 1000 mg × 3 times a day with a working diagnosis of «Acute pyelonephritis. Acute kidney injury in the resolution stage». Untimely diagnosis of the disease can lead to life-threatening complications: intestinal translocation syndrome, severe sepsis, multiple organ dysfunction syndrome. The above, dictates the need to inform doctors of the practical level of healthcare about the problem of pseudomembranous colitis, since it is known that with timely diagnosis of pseudomembranous colitis K and adequate anticlostridiosis therapy, it is possible to save the patient's life. It is necessary to inform doctors more widely about the possibility of an atypical course of the disease and to increase the alertness of doctors regarding the disease caused by pseudomembranous colitis, Clostridium difficile, antibacterial pneumonia, acute kidney injury.